A comprehensive review of the novel therapeutic targets for the treatment of diabetic cardiomyopathy - Arti Dhar; Jegadheeswari Venkadakrishnan; Utsa Roy; Sahithi Vedam; Nikita Lalwani; Kenneth S. Ramos; Tej K. Pandita; Audesh Bhat (Therapeutic Advances in Cardiovascular Disease, 2023)
Diabetic cardiomyopathy (DCM) is characterized by structural and functional abnormalities in the myocardium affecting people with diabetes. Treatment of DCM focuses on glucose control, blood pressure management, lipid-lowering, and lifestyle changes. Due to limited therapeutic options, DCM remains a significant cause of morbidity and mortality in patients with diabetes, thus emphasizing the need to develop new therapeutic strategies. Ongoing research is aimed at understanding the underlying molecular mechanism(s) involved in the development and progression of DCM, including oxidative stress, inflammation, and metabolic dysregulation. The goal is to develope innovative pharmaceutical therapeutics, offering significant improvements in the clinical management of DCM. Some of these approaches include the effective targeting of impaired insulin signaling, cardiac stiffness, glucotoxicity, lipotoxicity, inflammation, oxidative stress, cardiac hypertrophy, and fibrosis. This review focuses on the latest developments in understanding the underlying causes of DCM and the therapeutic landscape of DCM treatment.